Effectiveness of Social Skills Training to Improve Social Functioning Scores in Schizophrenia Patients at X Lawang Mental Hospital - Ratna, Dwi; Supriyanto, Irwan; Pratiti, Budi (Fakultas Kedokteran Universitas Brawijaya, 2024)
Disability can cause social dysfunctions that affect daily activities, social interaction, and work, which has a significant impact on the quality of life of schizophrenics so that they depend on other people. The use of pharmacotherapy alone is not enough; psychosocial interventions such as social skills training (SST) is needed to improve social functioning in schizophrenic patients. Incorporating social skills training (SST) into a multifaceted treatment and rehabilitation program is deemed significant. The study aimed to determine the effect of social skills training to improve social functions in schizophrenia patients in X Lawang Mental Health. This study used a pre-experimental design with one group pre-test and post-test. Of 40 patients with schizophrenia who were admitted to X Lawang Mental Health fulfilled the inclusion and exclusion requirements. Social function scores were measured using the Personal and Social Performance (PSP) instrument before and after the social skills training intervention. The level of significance of statistical tests is stated at p<0.05. Data analysis used the Wilcoxon test and linear regression. There was significant difference in social functioning scores between before and after social skills training with a value of p=0.000 (p<0.05). The results of the multivariate linear regression test showed that social skills training had a statistically significant effect to improve social function scores with a value of p=0.000. Social skills training has a significant effect to improve social functioning scores in schizophrenics at X Lawang Mental Health.